Preparation, In Vitro Evaluation and Characterization studies of Clozapine Nanosuspension - Amal Abdullah Mohammed; Shaimaa Nazar Abd Alhammid (Iraqi Journal of Pharmaceutical Sciences, 2025)
Clozapine (CLZ) is a tricyclic dibenzodiazepine, classified as an atypical antipsychotic agent. It belongs to the Biopharmaceutical Classification System (BCS) class II drug (High Permeability, Low Solubility), with a high first-pass effect. The current study used a technique called the solvent-antisolvent method to prepare a nanosuspension of clozapine with different stabilizers and solvents in an effort to increase the drug's solubility and dissolution. (Soluplus®, HPMC E15, PVA, Poloxamer 188, Poloxamer 407, PVP K30, PVP K90, and Tween 40) were used to produce the formula. Evaluations were done on particle size, PDI, zeta potential, and in vitro dissolution investigations. According to the data, all developed clozapine formulations had particle size values in the nano-size range. The best formula, A7, had a particle size of 80.43 nm and contained 1:3 Soluplus® as a stabilizer. Methanol was used as a solvent in a 1:5 ratio, with water acting as an anti-solvent, and a stirring speed of 1000 rpm was employed. The optimized freeze-dried nanoparticles underwent some characterization tests, including FTIR, XRD, and FESEM, which revealed smooth, uniform particles within the nano size. The location of the CLZ nanosuspension functional group was not altered by FTIR, while XRD revealed that clozapine had changed from a crystalline to an amorphous form. In conclusion, the solubility and dissolution rate of the drug were considerably increased when clozapine, which is weakly soluble in water, was prepared as a nanosuspension.